GRAIN DRYING I: PRESSURE LOSS IN SPOUTING BED - Condorhuamán C., Cesario (2002)
It has been obtained a experimental drop in pressure as a result of making flow air through a column of spouted bed loaded with wheat grains. A built column of stainless steel is used whose traversa section in a semicircular way has 152.4 mm of diameter, it finishes in a base truncated cone whose entrance hale is other 1 semi-circulate of 12 .5 mm of diameter and it has a height of 1.30 meters. The results are obtained to standard conditions of pressure and temperature, The flows of air vary between 9.9 and 52.2 cubic meters per hour and losses of pressure are obtained between 6.4 and 14.1 KPa/m, respectively.